The amazing Spider-man - Webb, Marc, (Director).; Ziskin, Laura; Arad, Avi; Tolmach, Matt; Vanderbilt, James; Sargent, Alvin; Kloves, Steven; Garfield, Andrew, 1983-; Stone, Emma, 1988-; Ifans, Rhys, 1967-; Leary, Denis; Scott, Campbell; et al. (Culver City, Calif. : Columbia Pictures, 2012)
Peter Parker finds a clue that might help him understand why his parents disappeared when he was young. His path puts him on a collision course with Dr. Curt Connors, his father's former partner.
Some copies may include a DVD.
Title from container.
Based on a work by: Stan Lee and Steve Ditko.
Release date: Nov. 9, 2012.
Originally released as a motion picture in 2012.
Special features: Deleted scenes; audio commentaries; stunt rehearsals; The Oscorp Archives - production art gallery.
Keywords: Spider-Man -- (Fictitious character) -- Drama; Heroes -- Drama; Comic books, strips, etc. -- Film and video adaptations; Action and adventure films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Drama; Feature films; Superhero films; Science fiction films